2010
DOI: 10.1523/jneurosci.2715-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

TRPA1 Is a Component of the Nociceptive Response to CO2

Abstract: In humans, high concentrations of CO 2 , as found in carbonated beverages, evoke a mixture of sensations that include a stinging or pungent quality. The stinging sensation is thought to originate with the activation of nociceptors, which innervate the respiratory, nasal, and oral epithelia. The molecular basis for this sensation is unknown. Here we show that CO 2 specifically activates a subpopulation of trigeminal neurons that express TRPA1, a mustard oil-and cinnamaldehyde-sensitive channel, and that these r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
119
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(122 citation statements)
references
References 36 publications
3
119
0
Order By: Relevance
“…To avoid mechanical or thermal co-stimulation, stimuli were embedded in a constantly flowing air stream (8 l/min) and applied via an olfactometer (Kobal, 1981;OM/2, Burghart Messtechnik GmbH, Wedel, Germany) that allowed for precise control of all parameters. CO 2 is converted into bicarbonate and protons (Tarun et al, 2003), which have been shown to excite trigeminal nociceptors via activating TRPV1 (Reeh and Kress, 2001) or TRPA1 (Wang et al, 2010) ion channels. This pain model is well established for clinical pharmacological pain research (eg, Kobal et al, 1990;Lötsch et al, 1998Lötsch et al, , 2006 including fMRI assessments (Oertel et al, 2008).…”
Section: Experimental Pain and Stimulation Protocolmentioning
confidence: 99%
“…To avoid mechanical or thermal co-stimulation, stimuli were embedded in a constantly flowing air stream (8 l/min) and applied via an olfactometer (Kobal, 1981;OM/2, Burghart Messtechnik GmbH, Wedel, Germany) that allowed for precise control of all parameters. CO 2 is converted into bicarbonate and protons (Tarun et al, 2003), which have been shown to excite trigeminal nociceptors via activating TRPV1 (Reeh and Kress, 2001) or TRPA1 (Wang et al, 2010) ion channels. This pain model is well established for clinical pharmacological pain research (eg, Kobal et al, 1990;Lötsch et al, 1998Lötsch et al, , 2006 including fMRI assessments (Oertel et al, 2008).…”
Section: Experimental Pain and Stimulation Protocolmentioning
confidence: 99%
“…Among the large family of transient receptor potential (TRP) ion-channels that includes the capsaicin (TRPV1) and menthol (TRPM8) receptors (Appendino et al, 2008;Inoue, 2005;Kim and Baraniuk, 2007;Woodard et al, 2007), the TRPA1 nociceptor has been implicated in the chemesthetic response to environmental irritants Macpherson et al, 2007b;McNamara et al, 2007) and even to CO 2 (Wang et al, 2010), as well as to weak organic acids (Wang et al, 2011). The TRPM5 channel has also been implicated in responses to irritants (Lin et al, 2008).…”
Section: ) Molecular Receptors For Trigeminal Chemesthesismentioning
confidence: 99%
“…In fact, TRPA1 is activated by a wide range of pungent and irritant compounds [125], including ingredients of various spicy foods, such as allyl isothiocyanate (mustard oil, wasabi and horseradish) [73], allicin and diallyldisulfide (garlic derivatives) [126], cinnamaldehyde (cinnamon), and environmental irritants and industry pollutants, such as acetaldehyde [127], formalin [128], hypochlorite, isocyanates [129], ozone [130], carbon dioxide [131], and acrolein [117], a highly reactive , -unsaturated aldehyde present in tear gas, and cigarette smoke [132]. Moreover, isofluorane [133], nicotine [134], NO donors [135], and cyclophosphamide [117] have been reported to activate TRPA1.…”
Section: Trpa1mentioning
confidence: 99%